Oral Administration of Heat-Treated Lactobacilli Modifies the Murine Microbiome and Reduces Citrobacter Induced Colitis - Warda, Alicja K.; de Almeida Bettio, Pedro H.; Hueston, Cara M.; Di Benedetto, Giulio; Clooney, Adam G.; Hill, Colin (Frontiers in Microbiology, 2020)
Significant evidence supports a relationship between the gut microbiome, inflammation, host response, and health, including the finding that a number of disorders are associated with disruption of the microbiome. In these disorders, a number of dietary interventions (including prebiotics, live probiotics, or heat-killed microbes) have been proposed to be curative or preventative agents. The use of heat-killed microbes has a number of benefits over living organisms, including reduced infection risk in vulnerable individuals, extended shelf life and the potential for use in combination with antimicrobial agents. We previously reported that murine chow supplemented with 5% ADR-159, a heat-treated fermentate generated by two Lactobacillus strains, altered both behavior and the microbiome of male mice. Now we show that ADR-159 fed female mice also display a similar microbiome shift as determined by 16S rDNA analysis. In particular, we observed a reduction of levels of Turicibacter and Clostridium sensu stricto. These subtle changes in the bacterial component of the microbiome were mirrored by changes in the virome. Extended consumption of the ADR-159 diet had no negative effect on general health and lipocalin 2 levels (LCN2; a proxy for inflammation), but we observed increased IL-17f and decreased IL-12α expression in the colon and decreased short chain fatty acid levels in the ADR-159 fed animals. Four weeks into the diet, half of the animals were dosed with Citrobacter to determine the effect of ADR-159 on infection and on pathogen induced colitis. Overall, our results suggest that while the ADR-159 diet does not prevent Citrobacter infection, it had an effect on Citrobacter-induced inflammation. In contrast to animals fed standard chow, ADR-159 fed animals did not show a reduction of small intestine length and increase of colon crypt depth, which occurred in control mice. These microbiological, histological, and immunological results provide evidence to support the impact of heat-treated microorganisms and their metabolites on the murine microbiome and health.